The psychological impact of COVID-19 on healthcare work force in the Middle East region C-S study - El-Gammal, Marwa Ahmed; Elgendy, Amira; Heidler, Petra; Owais, Tarek A.; Eltewacy, Nael Kamel; Hamza, Nouran; , the EARG group; Amir Rais, Mohammed; Ashraf, Reman; kamal abdou, Entesar; Sobhy Kiddees, Ereen; Abdelrazek Abdellah, Arwa; et al. (Frontiers in Psychiatry, 2023)
Introduction COVID-19, is one of the biggest challenges facing humanity in the 21st century (1). The pandemic outbreak as affected all human activities, starting with healthcare and medical service passing with economy and social relationships, as well as political, religious and cultural enactments (2). The healthcare workers were the most affected fighting in the frontline working longer hours under a high risk of being infected (3). This study aims to assess the depression, anxiety and stress levels of the healthcare workforce (physicians, nurses, pharmacists and dentists) in the Middle East and North Africa—MENA–region. Methods We invited healthcare workers in the Middle East to participate in our cross-sectional survey by answering to the DASS-21 questionnaire. Results A total of 4,845 healthcare workers participated in the study. The participants were from 11 countries as follows: 436 from Egypt, 430 from Algeria, 458 from Iraq, 453 from Jordan, 473 from Libya, 428 from Palestine, 419 from Saudi Arabia, 452 from Sudan, 451 from Syria, 424 from Tunisia, and 421 from Yemen. The doctors among the healthcare workers were 51.7%, 19.0% were from the nursing staff, 16.8% were pharmacists, and 12.5% were from dentists. The depression level among the healthcare workers was as follows: 29.1% were normal, 13.7% were mildly depressed, 26.9% were moderately depressed, 14.4% were suffering from severe depression, and the depression state was extremely severe for the last 15.9%. At the same time, 29.1% were suffering from no anxiety, while 6.9% were at a mild level, 22.3% were at a moderate level, 13.4% were at a severe level, and 28.3% were at an extremely severe level. For the stress levels, 38.6% were normal, 14.9% were suffering from mild stress, 20.3% were moderate, 17.4% were severe, and the stress level was extremely severe for the other 8.9%. Discussion This study indicates that in the Middle East and North Africa—MENA—region, the prevalence of depression, anxiety, and stress among the healthcare workforce during the COVID-19 pandemic was 70.9, 70.9, 61.4, respectively.